Clinical characteristics and management of headache in patients with myeloproliferative neoplasms - Shimoyama, Takashi; Yamaguchi, Hiroki; Kimura, Kazumi; Suzuki, Fumiaki; Hayashi, Toshiyuki; Wakita, Satoshi (Frontiers in Neurology, 2022)
Background Headache is frequently reported as a neurological manifestation of myeloproliferative neoplasms (MPNs), including polycythemia vera and essential thrombocythaemia. This study sought to clarify the clinical characteristics and response to treatment of headaches in patients with MPNs. Methods We prospectively studied 137 patients with MPNs. The following information was gathered to assess the features of headache at baseline and at follow-up (>6 months): (1) average duration of headache attacks, (2) number of headache days per month, (3) numerical rating scale (NRS), (4) Headache Impact Test-6 (HIT-6), and (5) Migraine Disability Assessment (MIDAS). We compared those parameters for headaches between the baseline and follow-up interviews according to the management. Results Thirty-seven (27.0%) patients had headache. The prevalence of headaches gradually decreased with increasing age (Age ≤ 49 years: 61.0%, 50–59 years: 38.5%, 60–69 years: 17.2%, 70–79 years: 5.1%, and ≥80 years: 0.0%, P < 0.001). Multiple logistic regression analysis showed that younger age, but not platelet counts or the JAK2 V617F mutation, was independently associated with headaches (Odds Ratios 2.004, 95% confidence intervals 1.293–3.108, P = 0.002). Scintillating scotomas were present in 22 (59.5%) of 37 patients with headaches, while four patients developed sudden headaches that lasted for only 0–10 min. Follow-up interviews were available for 31 (83.8%) of 37 patients with headaches. Twenty-one (67.7%) patients were treated with low-dose aspirin (100 mg once daily) [low-dose aspirin alone: n = 9; combined cytoreductive therapy: n = 12] for headache management. All parameters for headache [average duration of headache attacks, number of headache days per month, NRS score, HIT-6 score, and MIDAS score (all P < 0.001)] were significantly improved at follow-up in patients taking low-dose aspirin. However, there were no significant differences in these parameters of headaches in patients who did not receive low-dose aspirin. Conclusion Headaches is common in patients with MPNs, particularly in younger patients. MPN-related headaches may be managed by using low-dose aspirin and controlling MPNs.